Urine and Saliva: Relevant Specimens for Malaria Diagnosis? - Hwa Chia Chai; Kek Heng Chua (Diagnostics, 2022)
Blood remains the specimen of preference for malaria diagnosis, whether it is for microscopic, nucleic acid-based or biomarker detection of Plasmodium present in a patient. However, concerning the disadvantages of blood drawing, specimens that can be non-invasively collected under non-hygienic settings would come in handy for malaria diagnosis in endemic areas with limited resources. Although the current approaches using saliva or urine might not be as sensitive and specific as using blood, the potential of these two specimens should not be underestimated and efforts in developing diagnostic methods for Plasmodium detection specifically in these two specimens should continue without giving up. This review not only compiles and summarizes the sensitivity and specificity achieved by various detection approaches when using these samples for malaria diagnosis, it also intends to enhance the possibility of using saliva and urine for diagnostic purposes by describing how Plasmodium nucleic acid and antigens may likely be present in these samples. This review may hopefully encourage and motivate researchers in developing saliva- and urine-based diagnostic methods for Plasmodium detection to facilitate the control and eradication of malaria. In summary, the presence of Plasmodium DNA and antigens in urine and saliva makes these two specimens relevant and useful for malaria diagnosis.